ANALISIS IMPLEMENTASI SISTEM TANGGAP DARURAT KEBAKARAN DI KAWASAN PERMUKIMAN PADAT PENDUDUK KELURAHAN KAYU PUTIH, JAKARTA TIMUR (Studi Kasus di RW 016 Kelurahan Kayu Putih, Kecamatan Pulogadung, Kotamadya Jakarta Timur) - Sukmo, Rogo; Suroto, Suroto; Wahyuni, Ida (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Fire danger is the danger of an uncontrolled fire, threatening the safety of life and property. According to the US NFPA (National Fire Protection Association) during 2005 to 2009, 7040 cases of fires per year by fires household furniture with a loss of material until 442 million dollars. Fire in RW 016 overwrites RT 08, RT 04 and RT 05. The fire caused the fire coming from the stove exploded, resulting in the burning of 200 houses and 800 people were evacuated. The purpose of this study is to analyze the implementation of the fire emergency system in densely populated areas of Jakarta base on Perda DKI Jakarta No. 8 of 2008 in Kayu Putih, Pulogadung East Jakarta. This research is descriptive - qualitative with indeep interview approach and purposive sampling technique. Subjects of this study consist of 12 people, 9 as main informants and 3 as triangulationinformant. The results of this research are available Balakar, hydrants, emergency response training, exit facility,and there are no available emergency response procedures, fire extinguisher, smart alarm, portable pumps, fire engine, water tank and direction signs. There is available Balakar but do not yet have the organizational structure and division of duties. Emergency response procedures is not appropriate because of there is no emergency response procedures.Emergency response training has be implemted although one time only since Balakar formed. There are no Active protection like fire extinguisher (APAR), smart alarm, hydrants, portable pumps, motor fire, water tank. Lifesaving line like road signs out appropriate yet. Lifesaving form of exit is appropriate but not worth function. Assembly point during a fire are in compliance, but there are no signs that indicate a assembly point.